Identification of a homozygous missense mutation in LRP2 and a hemizygous missense mutation in TSPYL2 in a family with mild intellectual disability. (April 2016) - Vasli, Nasim; Ahmed, Iltaf; Mittal, Kirti; Ohadi, Mehrnaz; Mikhailov, Anna; Rafiq, Muhammad A.; Bhatti, Attya; Carter, Melissa T.; Andrade, Danielle M.; Ayub, Muhammad; Vincent, John B.; John, Peter
Abstract : Non-syndromic autosomal recessive intellectual disability (ID) is a genetically heterogeneous disorder with more than 50 mutated genes to date. ID is characterized by deficits in memory skills and language development with difficulty in learning, problem solving, and adaptive behaviors, and affects ∼1% of the population. For detection of disease-causing mutations in such a heterogeneous disorder, homozygosity mapping together with exome sequencing is a powerful approach, as almost all known genes can be assessed simultaneously in a high-throughput manner. In this study, a hemizygous c.786C>G:p.Ile262Met in the testis specific protein Y-encoded-like 2 ( TSPYL2 ) gene and a homozygous c.11335G>A:p.Asp3779Asn in the low-density lipoprotein receptor-related protein 2 ( LRP2 ) gene were detected after genome-wide genotyping and exome sequencing in a consanguineous Pakistani family with two boys with mild ID. Mutations in the LRP2 gene have previously been reported in patients with Donnai–Barrow and Stickler syndromes. LRP2 has also been associated with a 2q locus for autism (AUTS5). The TSPYL2 variant is not listed in any single-nucleotide polymorphism databases, and the LRP2 variant was absent in 400 ethnically matched healthy control chromosomes, and is not listed in single-nucleotide polymorphism databases as a common polymorphism. The LRP2 mutation identified here is located in one of the low-density lipoprotein-receptor class A domains, which is a cysteine-rich repeat that plays a central role in mammalian cholesterol metabolism, suggesting that alteration of cholesterol processing pathway can contribute to ID.